2002
DOI: 10.1080/08998280.2002.11927875
|View full text |Cite
|
Sign up to set email alerts
|

Dyspnea and Bilateral Interstitial Pulmonary Infiltrates in an Intravenous Drug User

Abstract: A 66-year-old man, a known intravenous heroin user for 45 years, presented to Baylor University Medical Center (BUMC) in May 2001 with a painful left upper arm after falling off a crate. A fractured left humerus was diagnosed, the arm was placed in a sling, and the patient was sent home. Upon reviewing the radiograph the following day, the attending radiologist noticed abnormal lung findings and called the patient, who reported a 1-to 2-month history of dyspnea on exertion. Several months earlier the patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The most dangerous one is respiratory depression. The fact remains, however, that intravenous oral morphine abuse has clear implications for infections, inflammations, and other severe side effects [109,110,111].…”
Section: Discussionmentioning
confidence: 99%
“…The most dangerous one is respiratory depression. The fact remains, however, that intravenous oral morphine abuse has clear implications for infections, inflammations, and other severe side effects [109,110,111].…”
Section: Discussionmentioning
confidence: 99%
“…In a Viennese study of a needle and syringe exchange programme, Haltmayer et al [56] found traces of morphine in 37% and of heroin only in 17%.Despite these new developments in morphine abuse, outcomes have rarely been studied systematically [33,[57][58][59][60][61]. Intravenous oral morphine abuse has clear implications for infections, inflammation and other severe side effects [62][63][64][65][66][67][68]. The high prevalence of morphine in opioid-positive urine samples in the last few years strongly suggest the need to focus on statistical analyses especially of this substance, as also of benzodiazepines, the consumption of which also appears to be increasing [33].…”
Section: Discussionmentioning
confidence: 99%